Examining the relationship between walkability and community resilience in Washington D.C. - Farley, Sarah; Farley, Sarah (Kansas State University, 2023)
To investigate the connection between walkability and community resilience in Washington D.C., data points across 180 census tracts were plotted and analyzed using a bivariate model. To understand why a positive relationship between walkability and community resilience did not exist in the data, as the literature indicated that it would, the researcher attempted to include qualitative data from key informants. However, it was not possible to acquire key informant data; thus, the researcher analyzed the data in terms of the literature to determine plausible explanations for the discrepancies, using explanation-building as a method. The initial but tentative hypothesis was challenged by the data, which ultimately showed no trend across the census tracts. Because of the lack of uniformity among definitions, existing research on the relationship between walkability and community resilience may not apply to the city of Washington D.C., which coincides with the lack of connection in the statistical data.
Keywords: Walkability; Community Resilience